Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Suppose we have matrices $A, B, C$ of dimensions $m \times n, m\times n, n \times l$ respectively. How can we prove $(A+B)\circ C = A\circ C + B \circ C$ (using the summation notation method?)

share|improve this question
1  
@LePressentiment Please don't edit someone's question just because the notation isn't perfectly standard. Some people use $\circ$ to emphasise that the multiplication is not usual multiplication of real numbers and it's perfectly acceptable to use such notation. –  Daniel Rust Aug 13 '13 at 14:26
add comment

3 Answers

up vote 0 down vote accepted

Tedious way...coefficientwise: $$ ((A+B)C)_{i,j}=\sum_{k=1}^n(A+B)_{i,k}C_{k,j}=\sum_{k=1}^n(A_{i,k}+B_{i,k})C_{k,j} $$ $$ =\sum_{k=1}^nA_{i,k}C_{k,j}+B_{i,k}C_{k,j}=\sum_{k=1}^nA_{i,k}C_{k,j}+\sum_{k=1}^nB_{i,k}C_{k,j} $$ $$ (AC)_{i,j}+(BC)_{i,j}=(AC+BC)_{i,j} $$ for all $1\leq i\leq n$ and all $1\leq j\leq l$. So $(A+B)C=AC+BC$.

share|improve this answer
add comment

Hint: Look at the linear maps represented by $A$, $B$ and $C$.

share|improve this answer
    
I'm mostly having trouble reconciling the summation notation. –  user67928 Mar 21 '13 at 23:07
add comment

Let $L = (A+B)C, R = AC + BC$.

With the Einstein summation convention, you have

$$L^i_j = (A+B)^i_k C^k_j = (A^i_k+B^i_k) C^k_j = A^i_k C^k_j + B^i_k C^k_j = R^i_j$$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.